Social support net for chemically dependents: ecomap as instrumental in health assistance - Cavalcante, Layana de Paula; Falcão, Rita de Souza Tomás; Lima, Helder de Pádua; Marinho, Angélica Mota; Macedo, Jaqueline Queiroz de; Braga, Violante Augusta Batista (Rev Rene, 2012)
The social support net is composed by the group of bonds related to the individual. Taking into account that the quality, as well as the quantity of these bonds can interfere in the person’s life, acting as positive or negative element, it was identified the need to know this net of relationships by the professionals that takes care of such individuals. It was aimed to assess the Ecomap of drug users assisted in a specialized service as instrumental of support for health care. This is a qualitative research carried out with 19 subjects assisted in a public service, through the Ecomap elaboration. Results show that CAPSad, family and religion constituted strong ties; work, colleagues and friends, links to be strengthened. Neighbors and former fellow drugs users were mentioned as stressors. Ecomap was an evaluation instrument that can be used to help the user to work his bonds, with special reference to those that need to be kept, broken or strengthened as social support.